A One-pot Multi-component Synthesis of some New Dihydropyrimidine Derivatives via Biginelli Condensations - Rostam R. Braiem (Zanco Journal of Pure and Applied Sciences, 2023)
The Biginelli Reaction is a one-pot acid catalyzed cyclocondensation of -keto ester, urea and aromatic aldehyde which leads to the synthesis of functionalized 3,4-dihydro-2(H)-pyrimidinones (DHPMs). These DHPMs (synthetic and natural) possess a wide range of pharmacological activities. A simple, efficient, and cost-effective method for the synthesis of 3,4-dihydropyrimidin-2(1H)-one by a one-pot three-component cyclocondensation reaction of a 1,3-dicarbonyl compound, an aldehyde and urea using HCl as catalyst is reported. The three-component condensation of an aldehyde, a -keto ester and urea in the presence of a catalytic amount of HCl, 3,4-Dihydropyrimidin-2(1H)-ones were synthesized in high yields. Recently much attention has been devoted towards dihydropyrimidine derivatives due to their significant therapeutic and medicinal properties. All the products in reaction obtained in good to very good yields by proceeding through a simple and efficient procedure. All the synthesized compound’s structure has been established by advanced spectroscopic data (FTIR, 1HNMR, and 13CNMR) and evaluated for their antibacterial activity against two types of bacteria (S. aureus and E.coli).